On educational problems of mathematics for the faculty of economics and management - Grinbergs, Emanuels (My University, 2013)
Problems concerning education of mathematics for the students of the Faculty of economics and managements are considered.
Keywords: mathematics, education; Latvijas Universitāte - vēsture